Geometric analysis of mandible using semilandmark in Hamdani and Awassi sheep - Demiraslan, Yasin; Demircioglu, Ismail; Guzel, Baris Can (Ankara Univ, 2024)
The aim of this study is to determine whether or not the breed and sex factors have an effect on the shape in the mandibles of Hamdani and Awassi sheep. A total of 31 mandibles were used. The samples were analyzed via geometric morphometric methods by using semilandmark. In the study, it was determined that the first principal component accounted for 36.52% of the total shape difference. According to principal component analysis, samples were clustered significantly in terms of breed; whereas, they were not clustered in terms of sex. In terms of the first principal component, the places where the shape differences were concentrated were the attachment sites of teeth to the mandible, between the second molar and ramus mandibulae, the processus coronoideus and the angulus mandibulae. The Mandibulae of Hamdani sheep had a higher body than the mandible of Awassi sheep. The mandibulae of male sheep was more voluminous than the mandible of female sheep, especially in the body area. Consequently, it is thought that the data obtained as a result of the study would serve as a reference for the ruminant mandible remains obtained from archaeological excavations.
Keywords: Breed; Morphometric; Semilandmark; Sex; Shape